PENGARUH MARKETING PUBLIC RELATIONS TERHADAP BRAND IMAGE DAN LOYALITAS PELANGGANDI STUDIO ALAM TV9 MATARAM - Ari Wahyuddin; Handry Sudiartha Athar (Master of Management, Mataram University, 2017)
This research is aimed at determining and explaining the effect of public relations marketing on the brand image and customers loyalty at Studio Alam TV9. This research is an explanatory research with quantitative approach. This research employed three variables of Public Relations Marketing, Brand Image, and Customers loyalty. The visitors of Studio Alam TV9 that have visited twice or more are the populations of this study. 110 visitors are the respondents of this research selected through purposive random sampling to which the questioners were distributed. The data were analyzed using path analysis. Based on that path analyzed the research showed that public relation marketing has direct and significant effect on Brand Image. And the brand Image has direct and significant effect on the customers loyalty. Beside that it is found that public relation marketing has indirect but significant effect of the customers loyalty through brand image. It is suggested that TV9 maintain and improve the public relation marketing ti improve the brand image and make the customers loyalty.Keywords: Marketing Public Relation, Brand Image, Customer Loyalty